2014
DOI: 10.1111/jopr.12209
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Marginal and Internal Fit of Crowns Fabricated Using Different CAD/CAM Technologies

Abstract: The SLM system demonstrated better marginal and internal fit compared to the two CAD/CAM grinding systems examined. Tooth type did not significantly influence the marginal or internal fit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 33 publications
1
46
0
19
Order By: Relevance
“…Ideal marginal adaptation causes less gingival irritation and cement dissolution. The deterioration of marginal fit over time can result in microleakage and plaque accumulation . It leads to the adherence of oral bacteria and may increase the risk of secondary caries, endodontic inflammation, postoperative sensitivity, and periodontal problems …”
Section: Introductionmentioning
confidence: 99%
“…Ideal marginal adaptation causes less gingival irritation and cement dissolution. The deterioration of marginal fit over time can result in microleakage and plaque accumulation . It leads to the adherence of oral bacteria and may increase the risk of secondary caries, endodontic inflammation, postoperative sensitivity, and periodontal problems …”
Section: Introductionmentioning
confidence: 99%
“…A recently published study that evaluated the marginal and internal fit, of two different milling systems, where a system used selective laser melting and the other a CAD/CAM system, found that the first system presented superior results for marginal and internal fit [28]. Maybe it would be interesting to investigate the polishing of the preparation and increase the number of groups to be evaluated, such as using the laser system mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate internal adaptation is especially important for placement of ceramic restorations because it results in homogeneous distribution of masticatory loads under stress [16, 17, 2628]. And when the ceramic restoration is well adapted chances of infiltration to occur in the margins of the tooth-restoration assembly are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…All ceramic, CAD/CAM full coverage restorations are becoming increasingly popular as this method provides expedient prosthesis fabrication with acceptable marginal accuracy . Compared to traditional laboratory‐fabricated cast restorations, CAD/CAM‐generated restorations rely more on adhesive technology, which proponents claim can compensate for loss of traditionally recommended preparation features .…”
Section: Introductionmentioning
confidence: 99%